RNA-Seq data provide new insights into the molecular regulation of breast muscle glycogen reserves, a key factor in muscle function and meat quality in chickens - Philippe Bochereau; Sarah Maman Haddad; Elisabeth Le Bihan-Duval; Cécile Berri (Poultry Science)
Research is needed to better understand the molecular mechanisms that influence muscle glycogen reserves in chickens due to their critical influence on muscle function and meat quality. In this study, breast muscle RNA sequencing data (RNA-Seq) were used to compare the transcriptomic profile of two original chicken lines divergently selected for breast muscle ultimate pH, which is a proxy for glycogen reserves. Weighted gene co-expression network analysis (WGCNA) of muscle and jejunum RNA-Seq data was also performed to highlight biological processes specifically involved in the gut-muscle dialogue that may contribute to the divergence in glycogen reserves between the two lines. Breast muscle RNA-Seq analysis of 4-week-old birds from the 15th generation of selection, in which glycogen reserves in the pHu- line were twice as high as that in the pHu+ line, revealed 2676 differentially expressed genes (Padj ≤ 0.05). Functional analysis of the genes overexpressed in the pHu- line highlighted enrichment in processes related to energy production from a wide range of substrates and pathways, as well as to processes involved in development of blood and lymph tissue. Diverse processes were enriched for genes overexpressed in the pHu+ line: muscle development and remodeling, lipid metabolism, immune response and inflammation, which suggested molecular changes much larger than those for carbohydrate metabolism. WGCNA revealed 64 modules of co-expressed genes. One, which contained 30 % genes expressed in the jejunum and 70 % genes expressed in the muscle, was correlated (P ≤ 0.05) with muscle glycogen reserves and several indicators of intestinal anatomy and health. Functional analysis of it showed an enrichment of processes related to transmission of nerve information and tissue oxygenation that seem to be involved in the gut-muscle dialogue that mediates establishment of breast muscle glycogen reserves. Finally, the study found that transcriptional regulations observed in muscle of the pHu+ line were similar to those in muscle afflicted with “wooden breast”, which highlighted a dysfunction of mitochondrial metabolism and suggested several potential gene markers for both conditions.